High-throughput virtual screening for organic electronics: a comparative study of alternative strategies. Issue 39 (23rd September 2021) - Omar, Ömer H.; del Cueto, Marcos; Nematiaram, Tahereh; Troisi, Alessandro
Abstract : We review how high throughput virtual screening can been used to navigate the landscape of materials for organic electronics. Abstract : We present a review of the field of high-throughput virtual screening for organic electronics materials focusing on the sequence of methodological choices that determine each virtual screening protocol. These choices are present in all high-throughput virtual screenings and addressing them systematically will lead to optimised workflows and improve their applicability. We consider the range of properties that can be computed and illustrate how their accuracy can be determined depending on the quality and size of the experimental datasets. The approaches to generate candidates for virtual screening are also extremely varied and their relative strengths and weaknesses are discussed. The analysis of high-throughput virtual screening is almost never limited to the identification of top candidates and often new patterns and structure–property relations are the most interesting findings of such searches. The review reveals a very dynamic field constantly adapting to match an evolving landscape of applications, methodologies and datasets.